Review on Sects and Religions in History of Iraq - Alfahham, Muayad Baqer Mohammed (International Journal of Islamic Business & Management, 2020)
Every tribe in Iraq has (Sunnis ,Sheia , the Yazidis, Turkmen, Armen,…) in its ranks. Every town and city have a mix of communities. My experience of Iraq, and that of all friends and relatives, is that of an amazing mix of coexisting communities, despite successive divide-and-rule regimes. For many centuries Iraq has been able to allow a religious, cultural and ethnic diversity to exist. Marred and disfigured as it undoubtedly has been from time to time by savage sectarian outbursts it has managed to stand the test of time. And now in a matter of months it is being swept away probably forever in an unimaginably brutal way. This is not only a terrible tragedy for each of those involved it is an historic tragedy for the world as yet another part of the finely woven tapestry of human complexity and coexistence is ripped to shreds. It is easier and quicker by far to destroy, and to call for destruction, than it is to build.